Root-zone cooling by cold energy from LNG regasification process for quality improvement of flower and bulb of Hippeastrum - C. Inkham (2020)
© 2020, Korean Society for Horticultural Science. In an attempt to improve growth and flowering of Hippeastrum ‘Apple Blossom’ grown in areas of tropical climate, the effect of root-zone cooling on root growth and flowering was investigated. Hippeastrum bulbs were harvested and transplanted to grow in planting-beds using expanded clay as the growing medium. The root-zone cooling methods were conducted using three treatments, namely T1) no cooling (NC) as the control treatment, the average root-zone temperature was 23 ± 2 °C; T2) short-term root-zone cooling (SC) at 11 ± 2 °C by circulating cool water through pipes installed on the beds for 13 weeks; and T3) long-term root-zone cooling (LC) at 11 ± 2 °C throughout the experiment (66 weeks after planting [WAP]). At 29 WAP, plant growth in terms of plant height and root length in the control treatment (NC) was less than the plant growth in other treatments, while at 66 WAP, plant height was not different between treatments. The root length gradually increased when the plant was grown by soil cooling at 11 ± 2 °C throughout the experiment (LC). In the first round of flowering (29 WAP), the results showed that the flowering percentage was not different between treatments. However, at the second round of flowering (66 WAP), plants grown under long-term root-zone cooling at 11 ± 2 °C (LC) had a higher flowering percentage (94.6%) than SC (33.3%), while the NC treatment plants did not flower. The bulb quality, photosynthetic rate, and stomatal conductance were discussed in this study. It was concluded that decreasing the temperature of the rhizosphere increased plant growth, improved the quality of flowers and bulbs, and also stimulated the flowering cycle of Hippeastrum. This result is beneficial for improving the quality of Hippeastrum cut flower in Thailand using a root-zone cooling system.